Integration of Gas Exchange With Metabolomics: High-Throughput Phenotyping Methods for Screening Biostimulant-Elicited Beneficial Responses to Short-Term Water Deficit - Antonucci, Giulia; Croci, Michele; Miras-Moreno, Begoña; Fracasso, Alessandra; Amaducci, Stefano (Frontiers in Plant Science, 2021)
Biostimulants are emerging as a feasible tool to counteract climate-change related yield and quality reduction under water scarcity. As they gain attention, the necessity to accurately assess phenotypic variables is emerging as a critical issue in their evaluation. In light of this, high-throughput phenotyping techniques are becoming more widely adopted. The main bottleneck in these techniques is represented by data management, which needs to be tailored on the complex, often multifactorial, data. This calls for the adoption of non-linear regression models capable of capturing dynamic data, as well as the interaction and effects between multiple factors. In this framework, a commercial glycinebetaine-based biostimulant (Vegetal B60, ED&F Man) was tested, distributed at a rate of 6 kg/ha. Exogenous application of glycinebetaine (GB), a widely accumulated and documented stress adaptor molecule in plants, has been demonstrated to enhance plant abiotic stress tolerance, drought included. Trials were conducted on tomato plants at flowering stage in a greenhouse. The experiment was designed as a factorial combination of irrigation (water stressed and well-watered) and biostimulant treatment (treated and control) and adopted a mixed phenotyping-omics approach. The efficacy of a continuous whole-canopy multichamber system coupled with GAMM to discriminate between water stressed plants under biostimulant treatment was evaluated. Photosynthetic performance was evaluated using generalized additive mixed modeling (GAMM), then correlated to metabolic profile. Results confirmed a higher photosynthetic efficiency of the treated plants, correlated to biostimulant-mediated drought tolerance. Furthermore, metabolomic analyses demonstrated the priming effect of the biostimulant for stress tolerance and detoxification and stabilization of photosynthetic machinery. In support of this, the over-accumulation of carotenoids was particularly relevant, given their photoprotective role in preventing the overexcitation of photosystem II. Metabolic profile and photosynthetic performance findings suggest an increased effective use of water (EUW) through overaccumulation of lipids and leaf thickening. The positive effect of GB on water stress resistance could be attributed both to the delayed onset of stress and the elicitation of stress priming through the induction of H2O2-mediated antioxidant mechanisms. Overall, the mixed approach supported by GAMM analysis could prove a valuable contribution to high-throughput biostimulant testing.